2010
DOI: 10.1080/03004430903507191
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of the teaching/learning process in preschoolers: theory of mind and age effect

Abstract: This study analysed the gradual emergence of the teaching/learning process by examining theory of mind (ToM) acquisition and age effects in the preschool period. We observed five dyads performing a jigsaw task drawn from a previous study. Three stages were identified. In the first one, the teacher focuses on the execution of her/his own task without paying any attention to the learner, who simply observes the teacher's actions. In the second one, the teacher recognises the learner's status, thereby allowing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In contrast, 5- and 6-year-olds rely more on verbal communication, especially abstract communication and elaborative teaching using verbal explanations (Strauss et al, 2002 ; Ziv et al, 2016 ; Ronfard & Corriveau, 2016 ; Ye et al, 2021 ). From ages 5 and 6, children are also better able to combine words and gestures to communicate with the learner, pay more attention to the learner's level of understanding and are more flexible in tailoring instruction to the learner's needs, goals and competence (Strauss et al, 2002 ; Davis-Unger & Carlson, 2008 ; Bensalah, 2011 ; Ziv et al, 2016 ; Gweon et al, 2018 ; Gweon & Schulz, 2019 ; Bridgers et al, 2020 ; Ye et al, 2021 ). These shifts are correlated with children's developing understanding of false belief (children's awareness that other people can hold misconceptions; Strauss et al, 2002 ; Davis-Unger & Carlson, 2008 ; Ziv et al, 2016 ; Ye et al, 2021 ).…”
Section: Human Teaching As a Cognitive Instinctmentioning
confidence: 99%
“…In contrast, 5- and 6-year-olds rely more on verbal communication, especially abstract communication and elaborative teaching using verbal explanations (Strauss et al, 2002 ; Ziv et al, 2016 ; Ronfard & Corriveau, 2016 ; Ye et al, 2021 ). From ages 5 and 6, children are also better able to combine words and gestures to communicate with the learner, pay more attention to the learner's level of understanding and are more flexible in tailoring instruction to the learner's needs, goals and competence (Strauss et al, 2002 ; Davis-Unger & Carlson, 2008 ; Bensalah, 2011 ; Ziv et al, 2016 ; Gweon et al, 2018 ; Gweon & Schulz, 2019 ; Bridgers et al, 2020 ; Ye et al, 2021 ). These shifts are correlated with children's developing understanding of false belief (children's awareness that other people can hold misconceptions; Strauss et al, 2002 ; Davis-Unger & Carlson, 2008 ; Ziv et al, 2016 ; Ye et al, 2021 ).…”
Section: Human Teaching As a Cognitive Instinctmentioning
confidence: 99%
“…Rieffe, Terwogt and Gowan (2005) indicated that learners start to display a sophisticated understanding of emotions from the age of five to six years as they begin to understand that HOEs are based on people's beliefs, that is their cognitive interpretation thereof, rather than an objective reality (Korkmaz 2011). Accordingly, based on this development of a more sophisticated understanding of emotion, authors such as Bensalah (2011) and Garfield, Peterson and Perry (2001) have indicated that ToM develops from around the same age (i.e. five years).…”
Section: Higher-order Emotion Identification As An Emotional Competency Skillmentioning
confidence: 99%
“…The ability to appreciate these two components of teaching has been found in neuro‐typically developing children (e.g. Bensalah, ; Bensalah, Olivier & Stefaniak, ; Ziv & Frye, ; Ziv et al ., ; Willis, ; Woodburn, ). For example, TD 5‐year‐olds, but not 3‐year‐olds, are able to distinguish teaching from imitation and appreciate that an agent's beliefs about the knowledge difference between a teacher and learner determines whether or not teaching will take place (Ziv & Frye, ; Ziv et al ., ).…”
Section: Introductionmentioning
confidence: 99%